Campaigning on Less Than a Shoe-String: An Ancient Egyptian Parallel to Abram's ‘Oath’ in Genesis 14.22–23 - Morschauser, Scott (Journal for the study of the Old Testament, 2013)
This article compares Abram's unusual oath to the king of Sodom in Gen. 14.22–23 with material from ancient Egypt. There, similar language is found in soldiers’ pledging to refrain from seizing ‘even a single sandal or ball of thread’ while on campaign. The patriarch's assertion, that ‘he would not take a thread or sandal thong, or anything that belongs to’ the king of Sodom, is to be viewed in like manner. Despite the ruler's generous offer that Abram receive a lion's share of plunder after rescuing Lot, the patriarch affirms that he will follow to the letter, his original oath regarding the disposition of booty, which he had sworn when setting out on his razzia (‘raid’) against Elam. Abram's self-sacrifice marks him as a ‘faithful servant’—one who is loyal to his pledge to God in the face of great temptation, and at considerable personal cost to himself.